2020
DOI: 10.1038/s41598-020-64158-2
|View full text |Cite
|
Sign up to set email alerts
|

Ly6cLo non-classical monocytes promote resolution of rhesus rotavirus-mediated perinatal hepatic inflammation

Abstract: Perinatal hepatic inflammation can have devastating consequences. Monocytes play an important role in the initiation and resolution of inflammation, and their diverse functions can be attributed to specific cellular subsets: pro-inflammatory or classical monocytes (Ly6c Hi ) and pro-reparative or non-classical monocytes (Ly6c Lo ). We hypothesized that inherent differences in Ly6c Hi classical monocytes and Ly6c Lo non-classical monocytes determine susceptibility to perinatal hepatic inflammation in late gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 51 publications
2
25
1
Order By: Relevance
“…As we see here, Ly6c, a marker of classically activated monocyte/macrophages [ 33 , 34 ], is also a good marker to identify blood vessels in mice.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As we see here, Ly6c, a marker of classically activated monocyte/macrophages [ 33 , 34 ], is also a good marker to identify blood vessels in mice.…”
Section: Discussionmentioning
confidence: 88%
“…Ly6c (lymphocyte antigen 6 complex, locus C1) is a monocyte/macrophage cell differentiation antigen commonly used to differentiate classical monocytes (Ly6c high ) from non-classical ones (Ly6c low ) [ 33 , 34 ]. Alliot et al, in 1998 [ 30 ], showed that Ly6c was expressed in the blood vessels of the mouse brain but not in microglial cells, and we wondered whether the same was true for the healthy and diseased retina.…”
Section: Introductionmentioning
confidence: 99%
“…Individual CMPs and TMPs were distinguished based on the expression of CD34, Fc1R, Flt3, Ly6C, and CD115 ( Figure 1a,b )[12]. Since our previous work demonstrated a limited role for T and B lymphocytes in the pathogenesis of PLI[4], lymphoid progenitors were not quantified in this study. We first quantified the lineage-negative (Lin -ve ) compartment in the liver and found that the percentage and number of Lin -ve cells did not differ significantly between P3 and P14 liver ( Figure 1c ) and the number of specific HSPC populations, including CMPs, and TMPs, were significantly lower at P14 than at P3 ( Figure 1c,d ).…”
Section: Resultsmentioning
confidence: 99%
“…All HSPCs were identified from flow plots as shown in Figure 3a . Mature populations were identified using a previously published gating strategy[4]. PLI significantly increased the number of Lin -ve cells in the liver ( Figure 3b ), which was reflected in downstream HSC LT s and CMPs ( Figure 3c ).…”
Section: Resultsmentioning
confidence: 99%
“…This proposition is made because some Ly6C + cells are apoptosis-prone populations [ 57 ]. Ly6C + immune cells are also known to perform both proinflammatory and immunosuppressive functions [ 58 , 59 ]. As the EBIS is considered a fine-tuned inflammatory as well as an immunosuppressive area, it is expected that Ly6C + decidual cells may behave like local innate immune cells with pro-inflammatory and immunosuppressive roles supportive of embryonic survival.…”
Section: Discussionmentioning
confidence: 99%